2021
DOI: 10.3389/fmicb.2021.764787
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Ceftriaxone-Resistant Salmonella in Children’s Hospital in Hangzhou, China

Abstract: The non-Typhi Salmonella (NTS) infection is critical to children’s health, and the ceftriaxone is the important empirical treatment choice. With the increase resistance rate of ceftriaxone in Salmonella, the molecular epidemiology and resistance mechanism of ceftriaxone-resistant Salmonella needs to be studied. From July 2019 to July 2020, a total of 205 NTS isolates were collected, 195 of which (95.1%) were cultured from stool, but 10 isolates were isolated from an extraintestinal site. Serogroup B accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Fortunately, the observed frequencies of resistance to monocyclic β-lactam antibiotics (aztreonam) and third and fourth generation cephalosporins were lower when compared to data from other studies [27,29,31]. Luckily, the distribution of MDR strains in our study was lower than reports in Argentina [30], Iran [37], Philippine [38], USA [33,39], and parts of China [31,35], indicating that the third-and fourth-carbapenems could be still effective for the clinical therapy of Salmonella infections.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Fortunately, the observed frequencies of resistance to monocyclic β-lactam antibiotics (aztreonam) and third and fourth generation cephalosporins were lower when compared to data from other studies [27,29,31]. Luckily, the distribution of MDR strains in our study was lower than reports in Argentina [30], Iran [37], Philippine [38], USA [33,39], and parts of China [31,35], indicating that the third-and fourth-carbapenems could be still effective for the clinical therapy of Salmonella infections.…”
Section: Discussioncontrasting
confidence: 70%
“…The reason may lie on the regional or strain difference. Meanwhile, our study showed that the resistance rates to cipro oxacin and levo oxacin were relatively lower than those in China [27,35], but it was higher when compared to data from Korea [34], USA [33], and Australia [36], suggesting the potential for treatment failure in patients treated with uoroquinolones in our country. Fortunately, the observed frequencies of resistance to monocyclic β-lactam antibiotics (aztreonam) and third and fourth generation cephalosporins were lower when compared to data from other studies [27,29,31].…”
Section: Discussionmentioning
confidence: 54%
“…Resistance to ceftriaxone is most commonly mediated by a cephalomycinase (CMY) encoded by the bla CMY gene family [ 52 ]. The susceptibility test in the current report confirmed the resistance of all the isolates studied to CRO.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA of all the isolates was extracted by a QIAamp DNA Mini Kit (QIAGEN, Hilden, Germany) and subjected to whole-genome sequencing on the Illumina HiSeq xTen platform (Illumina, San Diego, CA, USA) with a 150 bp paired-end strategy, as previously described [ 25 ]. Isolates CHN24001 and CHN24025 were further subjected to long-read sequencing by a MinION sequencer device (Nanopore Technologies, Oxford, UK) with a 1D flow cell.…”
Section: Methodsmentioning
confidence: 99%
“…cgMLST was performed by Ridom seqsphere (version 6.0.0, Ridom GmbH, Münster, Germany), as previously described [ 31 ]. The randomly selected 92 isolates from different continents along with the 5 isolates in this study were imported for phylogenetic relationship analysis based on their single-nucleotide polymorphisms (SNPs) using Snippy [ 25 ]. The genome of C234 was used as a reference (accession number: SAMN15868954) [ 9 ], and the tree was illustrated by iTol ( (accessed on 22 August 2022)).…”
Section: Methodsmentioning
confidence: 99%